Social Relations in Human and Societal Development - (:unkn) unknown (Basingstokes (Hampshire, UK): Palgrave Macmillan, 2015)
Social interaction is part of human life and is the engine which drives an individual's psychological development, creating changes on all levels of society. Through a collection of essays by internationally renowned academics from a range of disciplines, including social psychology, international relations and child development, Social Relations in Human and Societal Development examines the effect of this integral force on human life. Each chapter explores the role of social relations in a particular domain to provide a broad understanding of the role of social relations in human and societal development.
Keywords: relations sociales développement sociétal et humain psychologie sociale et culturelle